A Study of Analyzing Oral and Written Feedback in Promoting Learning of Mathematics - Fatima, Roohi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
"Feedback is conceptualized as information provided by an agent (e.g., teacher, peer, book, parent, self, experience) regarding aspects of one‘s performance or understanding."(Timperley and Hattie, 2007) One of the major banes in Teaching and Learning of Mathematics lies in the the crude methods of assessment that encourage the perception of mathematics as mechanical computation (NCF 2005). Every classroom of a school follows the same routine of teaching where the teacher gives instructions, provide work to do and then check it in their own way. There is only one type of checking which our teacher, generally, follows in the classroom. This checking is conducted in the form of marking ticks for correct solutions and crosses for incorrect solutions. But the assessment of having right and wrong is not beneficial for students; the assessment should be followed with the feedback, which gives detailed information to students about concepts, misconception which led to the wrong answer and so on.  Rama Prasad (1983) defined feedback as information about the gap between the actual level and the desired level of performance, which in turn leads to corrective action to minimise the gap. The motive behind the feedback is to make the child aware of the desired goal or action that is demanded or the answers of the questions like Where am I going What is my goal? How am I going? Where to next? etc. Effective feedback provides the learner with two types of information: verification and elaboration. Verification is defined as the simple judgment of whether or not an answer is correct, and elaboration is the informational aspect of the message, providing relevant cues to guide the learner towards a correct answer.  In this article, the author is attempting to find out whether the feedback can be used to facilitate the teaching-learning process of mathematics or not For this, she conducted an experimental study. The focus of this study is to find out whether the oral and written feedback make any difference in the performance of students if it is provided after the tasks they had formed in their classes. This study was conducted to see the effect of enhanced feedback versus traditional feedback. Apart from this, she also tries to discuss the answers to the following questions: What is the feedback?  What are the different methods of giving feedback?  Does feedback facilitate meaningful learning in mathematics?  The objective is that the process of seeking the answers to these questions will necessarily involve a significant discussion on the effectiveness of feedback in the teaching-learning process of mathematics.